The 14Th General Election (GE-14) and the Defeat of Barisan Nasional in Silam - Wan Shawaluddin Wan Hassan; Nordin Sakke; Jusman Aman Setia; Diana Peters (2018)
Since BN/UMNOs entry into East Malaysia, Sabah and Sarawak were often referred to as BN/UMNOs fixed deposit states following their victory during the 1994, 1998, 2004, 2008 and 2013 general elections. However, GE-14 saw the change in BN’s hold on Sabah when Parti Warisan came to power. In the Parliament Seat of Silam, BN lost 4-0 to Parti Warisan. This article looks into the factors that contributed to this defeat amongst which was the lack of attention on the squatter problems, nepotism, land issues, ESSCOM, rising costs of living and 1MDB. Qualitative methods such as interviews, observation, and secondary data i.e. newspapers, journal articles, books and internet were used. Interviews with contending candidates, political members from both BN and Parti Warisan, as well as the general community in Silam was carried out. The findings observed was the failure of BN to heed lessons from past elections whereby voters in Sabah would rationally vote to change governments if they were not satisfied with the government of the day, as was the case in 1976 (USNO), 1985 (Berjaya) and 1994 (PBS). It was this lack of attention to history which saw BN’s lost over its stronghold in Silam during GE-14.